Is the tourism–economic growth nexus time-varying? Bootstrap rolling-window causality analysis for the top 10 tourist destinations. Issue 24 (21st May 2018) - Shahbaz, Muhammad; Ferrer, Román; Shahzad, Syed Jawad Hussain; Haouas, Ilham
ABSTRACT: This article explores the time-varying causal nexus between tourism development and economic growth for the top 10 tourist destinations in the world, namely China, France, Germany, Italy, Mexico, the Russian Federation, Spain, Turkey, the UK and the United States of America, over the period 1990–2015. To that end, a bootstrap rolling window Granger causality approach based on the modified Granger causality test is used. A new index for tourism activity which combines via principal component analysis the commonly used tourism indicators is also employed. The results of the bootstrap rolling window causality tests reveal that the causal relations between tourism and economic growth vary substantially over time and across countries in terms of both magnitude and direction. It is shown that the causal linkages tend to be more pronounced for a large group of countries following the global financial crisis of 2008. Additionally, Germany, France and China clearly stand out as the countries with the weakest causal nexus, while the UK, Italy and Mexico emerge as the countries that have the strongest causal links. These results have particularly important implications for policymakers.